Transformasi Pendidikan Guru SD: Analisis Program TEMA PGSD dalam Meningkatkan Kualitas Pengajaran dan Prestasi Siswa - M. Hikmal Yazid (Jurnal Pendidikan Guru Sekolah Dasar, 2023)
In response to the imperative need for enhancing primary school education, this study delves into the transformative impact of the TEMA PGSD program on the professional development of elementary school teachers. The article's objective is to analyze how the program contributes to elevating teaching quality and student achievement. Through a mixed-methods approach, combining participant surveys and in-depth classroom observations, this research investigates the practical implications of TEMA PGSD. The findings underscore a notable positive shift in pedagogical practices among participating teachers, leading to observable improvements in student performance across various subjects. With a concise yet comprehensive overview of the program's methodology, which prioritizes interactive learning and practical application, this study provides valuable insights for educators, policymakers, and researchers. The background highlights the pressing need for effective teacher training, setting the stage for the relevance of the TEMA PGSD initiative. The article concludes by emphasizing the program's potential as a transformative model for primary school teacher education. This research not only addresses a critical gap in current educational strategies but also offers practical solutions to enhance the overall quality of primary education, laying the groundwork for future advancements in teacher professional development.